Implementasi Asesmen Diagnostik dalam Kurikulum Merdeka di SMAN 1 Kabun - Desi Arni Natalina Br Siburian; Muhammad Mukhlis (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The teacher's important role is in planning a good assessment so that it can be given to students to measure their basic abilities, the implementation of the assessment, as well as the results and evaluation/follow-up to students after carrying out the Diagnostic Assessment. What things do teachers do to produce a good assessment as well as the obstacles and constraints experienced while preparing and implementing this Diagnostic Assessment. The research method used in this research is a descriptive qualitative research method. Data collection techniques in this research are interview and documentation techniques. The purpose of this research is to find out the extent of preparations made by educators to implement and carry out Diagnostic Assessments in schools from the preparation, implementation stages to the results of evaluations and follow-up carried out as well as knowing the weaknesses and strengths of each student. The benefit of this research is to obtain information about the implementation of Diagnostic Assessment at SMA N 1 Kabun. Find out what obstacles were experienced during the implementation of the Diagnostic Assessment at SMA N 1 Kabun. After knowing this, educators will easily determine the learning model that will be carried out on students. From the results of this research, the Diagnostic Assessment in the Merdeka Curriculum at SMA N 1 Kabun really helps teachers in teaching, and makes students know and can measure their own basic abilities, and students also become more active and enthusiastic in learning. Even though teachers have various obstacles and obstacles in implementing this Diagnostic Assessment, so far the implementation has been quite good and has shown maximum results.